The kings and queens of roam - Wallace, Daniel, 1959- (Simon & Schuster, 2013)
When their parents die an untimely death, a blind, naïve younger sister becomes wholly dependent on her bitter and conniving older sister, who overprotectively imparts stories of a brutal and dangerous world until the younger sister makes a surprising choice.